MODEL PENGEMBANGAN BISNIS UMKM: CSR PT. PERTAMINA PATRA NIAGA TERNATE DALAM PROGRAM INKUBASI BISNIS JAMBULA - Mas'ud, Ibnu (Institut Agama Islam Negeri Ternate, 2024)
Jambula Business Incubation is a program conducted by PT Pertamina Patra Niaga Fuel Terminal Ternate. The program is a collaboration between community group stakeholders, the company and the local government that seeks to optimize the potential of of micro, small and medium enterprise business groups in Jambula. Until 2021, several local business groups in Jambula were formed including, 1) Bubula Fish Processed, 2) Bubula Store, 3) Pertamina Enduro Workshop, 4) Bubula Café. The four groups are included in the Jambula Business Incubation program which is definitively FT Ternate's CSR fostered partner, basic improvement efforts are made between the company and the Jambula Business Incubation management group. The program includes mentoring, improvement of facilities and infrastructure and competency management training for of micro, small and medium enterprise which is an effort to provide opportunities and economic equality in the village and employment opportunities. The community as a subject has a role and responsibility to jointly encourage the success of business development in their area based on empowerment. Data collection in this study through literature studies, observation of sources and previous research and using a purposive sampling approach, namely the Jambula Business Incubation management group as the key informant in this study. The Business Incubation Program managed to get various awards from the city to the national level.Keywords: Business Incubation; CSR; Stakeholders; Empowerment.